Trading in Influence: Criminal Law and Criminal Procedure Aspects - MAMITOVA, Zhanat Askarovna; AGBAYEVICH, Yerbol Omarov; TALKIBAYEV, Askar Bolatovich; IRUBAYEVA, Aigul Tanabugovna (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The paper deals with the practice of criminalization of trading in influence by the lawmakers of the former Soviet Union and other foreign countries. Comparative approach to the solution of the criminal policy problems of the Republic of Kazakhstan on the fight against corruption was supported by the conducted sociological researches. The problems of the qualification in the law-enforcement activities were considered from various angles with regard to which applicable and inapplicable attributes of trading in influence in the context of the Kazakhstan legal environment were depicted. In particular, the comparison of this criminal action with the other crimes was carried out, in the course of which trading in influence appeared to be a separate crime with its peculiar objective and subjective attributes. Besides, the authors considered the problems of international cooperation in the absence of criminalization of trading in influence by the legislation of Kazakhstan. Particularly, they also developed the legal grounds for refusal of rendering legal assistance in legal cases, including for reasons of absence of the crime dual criminality. The research of the international conventions and the national legislation allowed revealing the problems of regulating the cooperation in domestic standards, as well as suggesting their bringing to conformity with the requirements of the United Nations Convention against Corruption. As a result of the research the authors formulated the conclusion about the necessity of incorporating the ‘Trading in Influence’ separate crime components to the Criminal Code of the Republic of Kazakhstan, as well as offered the draft of the description of the punishable offence.
Keywords: implementation, United Nations Convention against Corruption, international contracts, trading in influence, crime, international cooperation, rendering legal assistance, confiscation, extradition, dual criminality